Antarctic circumpolar modes in a coupled ocean-atmosphere model - Marsland, SJ; Latif, M; Legutke, S (2003)
Eastward-propagating patterns in anomalous potential temperature and salinity of the Southern Ocean are analyzed in the output of a 1000-year simulation of the global coupled atmosphere-ocean GCM ECHO-G. Such features can be associated with the socalled Antarctic Circumpolar Wave (ACW). It is found that time-longitude diagrams that have traditionally been used to aid the visualization of the ACW are strongly influenced by the width of the bandpass time filtering. This is due to the masking of considerable lowfrequency variability that occurs over a broad range of time scales. Frequency-wavenumber analysis of the ACW shows that the eastward-propagating waves do have preferred spectral peaks, but that both the period and wavenumber change erratically when comparing different centuries throughout the simulation. The variability of the ACW on a variety of time scales from interannual to centennial suggests that the waiting time for a sufficient observational record to determine the time scale of variability of the real world ACW (and the associated decadal time scale predictability of climate for southern landmasses) will be a very long one. Â© Springer-Verlag 2003.